Recruiting general practitioners for palliative care research in primary care: real-life barriers explained - Leysen, B. (BMC Fam Pract, 2019)
BACKGROUND: The implementation of early palliative care within a primary care setting is a recent academic topic. Recruiting General Practitioners (GPs) to participate in a palliative care study can be challenging. The pro-Spinoza project implemented a Care Pathway for Primary Palliative Care in 5 areas in Belgium. During this project, the feasibility of the recruitment of GPs and palliative care patients was evaluated. METHODS: The recruitment process was recorded in detail via an electronic logbook combining quantitative and qualitative data. Quantitative recordings included the contact types and the number of contacts with eligible GPs and were analysed descriptively. Qualitative recordings included field notes with feedback from the GPs and other stakeholders and were thematically analysed starting from the Grol and Wensing framework for professional behaviour change. RESULTS: Of 4065 eligible GPs working in 5 areas under research, 787 GPs (19%) were contacted individually, 398 GPs (9,8%) were contacted face-to-face and most of these 398 GPs showed high interest in the topic. 112 GPs (2,8%) signed the collaboration agreement, but finally only 65 GPs (1,6%) delivered at least a completed baseline-questionnaire. Despite the initial interest in participating, the unpredictable and busy daily workloads of the GPs, as well as inexperience with research protocols, impeded the ability of the GPs to fully engage in the study. This resulted in the high dropout rate. Participating GPs reported that they had underestimated the effort required to effectively participate in the project. CONCLUSIONS: Recruitment of GPs to palliative care research is challenging. Primary care is a vital service to engage in palliative care research however the practical limitations reduce the ability of the service to effectively engage in the research. More research is needed to determine how GPs might be better supported in research. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02266069, Registered 16th October 2014, retrospectively registered.